The Relationship Between Socioeconomic Status and Public Perception of Waste Management and the Quality of Environmental Sanitation in Makassar District, Makassar City - St. Nuryati R; Firdaus Daud; Halimah Husain; Muhiddin Palennari; Muhammad Arsyad (Postgraduate, University of Mataram, 2026)
This study aims to analyze socioeconomic status, public perceptions of waste management, and environmental sanitation quality in Makassar District, Makassar City, as well as examine their relationships. The research used an ex post facto survey method with a proportional cluster sampling technique, involving 323 households. Data were collected through Likert-scale questionnaires and documentation, then analyzed using descriptive and inferential statistics (simple and multiple linear regression) with SPSS 26.0.The results show that socioeconomic status, public perception, and environmental sanitation quality are all in the moderate category. Partially, socioeconomic status has a positive and significant relationship with environmental sanitation quality, contributing 23.9%, while public perception contributes 2.10%. Simultaneously, both variables have a positive and significant effect with a total contribution of 23.4%. In conclusion, improving environmental sanitation quality requires simultaneous efforts through socioeconomic empowerment and strengthening public awareness of waste management.